1996
DOI: 10.1002/anie.199622591
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Steroids with the Heck Reaction

Abstract: By means of a double Heck reaction the pharmacologically interesting estrapentaene 3 can be synthesized regio‐ and stereoselectively from (Z)‐(2‐bromoethenyl)‐bromobenzene (1) and the indene derivative 2. A variety of novel steroids can be obtained by variation of the benzene and indene components and subsequent functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Recently, Tietze and coworkers with the aim of developing shorter and efficient synthetic routes for accessing steroidal molecules (Estrone derivative, 21), carried out a step-wise double Heck reaction between (Z)-(2-bromoethenyl)bromobenzene and hexahydro-1H-indene derivative (Scheme 20). 83 One of the key features of the protocol was the highly regio-and stereoselective Heck reaction with the C-C bond formation taking place anti to the angular methyl group. This step was then followed by another ring closing intramolecular Heck reaction affording the Scheme 18 (+)-g-Lycorane (18) synthesis via regio-and enantioselective allylation reaction.…”
Section: Heck Reactionsmentioning
confidence: 99%
“…Recently, Tietze and coworkers with the aim of developing shorter and efficient synthetic routes for accessing steroidal molecules (Estrone derivative, 21), carried out a step-wise double Heck reaction between (Z)-(2-bromoethenyl)bromobenzene and hexahydro-1H-indene derivative (Scheme 20). 83 One of the key features of the protocol was the highly regio-and stereoselective Heck reaction with the C-C bond formation taking place anti to the angular methyl group. This step was then followed by another ring closing intramolecular Heck reaction affording the Scheme 18 (+)-g-Lycorane (18) synthesis via regio-and enantioselective allylation reaction.…”
Section: Heck Reactionsmentioning
confidence: 99%
“…Scientific and industrial applications of Heck reactions catalyzed by palladacycle 1a have been reported for the total synthesis of estrone steroid derivatives [29], the anti-leukaemia alkaloid cephalotoxin [30]. The vinylation of 2-bromo-6-methoxynaphthalene with ethylene to a single product [31] has been applied on the pilot plant-scale for the synthesis of Naproxen by Hoechst (Scheme 4).…”
Section: The Heck Reactionmentioning
confidence: 99%
“…[11] However, a total synthetic approach is indispensable in order to gain access to analogs that cannot be derived from natural steroids. [14,15] A similar approach has also been successfully employed in the synthesis of -homoestradiols [16] and novel aza-heterocycles. [14,15] A similar approach has also been successfully employed in the synthesis of -homoestradiols [16] and novel aza-heterocycles.…”
Section: Introductionmentioning
confidence: 99%